Lista nacional de recomendação de dispositivos oscilométricos de pressão arterial: estudo transversal exploratório - Sousa, Francisco Moises Ferreira de (2022)
The correct measurement of blood pressure (BP) is essential for the diagnosis and control of arterial hypertension (AH), since, normally, its alteration is the first sign of the disease. There are ways to measure BP, including the oscillometric method, which uses automatic measuring devices. However, even with the availability of this method, there is still resistance among health professionals to using automated measurement, perhaps due to doubts about the quality and accuracy of the equipment available in Brazil. That said, there is an urgent need to establish means of informing the scientific community and general population about which automatic blood pressure measuring devices have been tested and found to have acceptable accuracy. Thus, the objective was to structure a national list with automatic devices for measuring blood pressure in the arm, for clinical and home use, marketed until 2021 in Brazil and approved in clinical validation studies. This is an exploratory cross-sectional study that used secondary data from the National Institute of Metrology, Quality and Technology (INMETRO) in the period 2002 - 2021. Data were collected in 3 stages, using the ordinances of the Legal Metrology Board (DIMEL) and the international lists of automatic PA devices. In the INMETRO database, a total of 74 DIMEL ordinances of automatic arm blood pressure devices, for clinical and home use, marketed in Brazil, were screened. Regarding arm devices that can be sold in Brazil, 50 (68%) devices were not validated with clinical studies. Altogether there are 24 devices that can be sold in Brazil and are validated. Therefore, it was concluded that in Brazil there are several companies that provide automatic blood pressure measurement devices, however most of these brands do not provide validated devices. In addition, the developed list will make it easier for consumers to choose a quality device. Also noteworthy is the pioneering nature of the study on the subject in Brazil, considering that it has not been highlighted so far.